The Academics at Stefan Batory University in Vilnius During the Interwar Period - Przeniosło, Małgorzata (Respectus Philologicus, 2013)
In the Second Polish Republic, only professors and associate professors (docents) working atuniversities were referred to as academics. This paper presents issues related to theiremployment. In the interwar period, the rules for employing academics were stated in the lawsof academic schools. There were two such acts at the time, which defined the rules for promotion to associate and full professorships. The manner of the appointment was based on the existence of a limited number of such chairs. All professorships were set up by the Polish government. The laws of academic schools also described the habilitation procedure, which led to receiving permission to lecture and use the academic title of docent. In this paper, general reflections on hiring academic teachers at universities are supported by examples fromStefan Batory University. I determined the size of the two employed groups, professors and docents, at the University between the wars. 138 persons worked there as professors—the largest number in 1937–38—and 70 were docents, with a maximum in one academic year of 11. I also describe issues regarding their scientific research (philosophers, literature specialists, and the academics from the Faculty of Medicine had the greatest achievements) and didactic and organizational work, as well as their salaries. I devote some attention to their private lives and non-academic activities as well (especially in relation to the most famous among them). My deliberations are based on archives and printed sources generated by SBU.
Keywords: Universities in the Second Polish Republic; Academic Teachers; Professors; Associate Professors; Docents